PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA BONEKA TANGAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TEMA 5 PENGALAMANKU KELAS II SEKOLAH DASAR - Sri Wahyuni M Gaga; Budi Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
This study aims to apply the Role Playing Learning Model assisted by hand puppet media to improve the learning outcomes of class II students of MIS Al-Fitrah Oesapa for the 2021/2022 academic year. Based on the results of observations and interviews at MIS Al-fitrah Oesapa conducted with the homeroom teacher for class II, it was found that in the learning process the teacher had not found a learning model that could increase students' enthusiasm for learning. The purpose of education is not achieved optimally, and causes student learning outcomes not to reach the KKM, it can be seen from the results of observations with the homeroom teacher II, from 20 class students there are 9 students who have not reached the school KKM (KKM 60). The research was conducted in 2 cycles. Based on the results of the tests conducted in the first cycle, it was found that there were still many students who had not reached the KKM. Where Cycle I achieved completeness of 62% and cycle II achieved completeness of 100%. The implications of this study are 1) the application of a role playing learning model assisted by hand puppet media